Perancangan Baru Panti Sosial Karya Wanita Di Kota Bandung Dengan Pendekatan Biofilik - Hanifa, Ghazala; Firmansyah, Rangga; Arief Hapsoro, Nur (eProceedings of Art & Design, 2024)
The Social Working Women's Fund (PSKW) is a government effort to help homeless women and Susila Tuna Women (WTS) return to normal life in accordance with social norms. PSKW's mission is to provide treatment and rehabilitation, enhance guidance, service, and reintegration into society. Bandung is a problem of prostitution, and women's welfare institutions have great potential to provide assistance and support to women engaged in prostitution or being victims of human trafficking. Rehabilitation that not only focuses on the religious aspect, but also involves skills training, psychological support, education, and the development of a positive environment, will be a more effective step. Thunfish women undergoing social rehabilitation often have traumatic backgrounds, low self-esteem, illicit substance addiction, and difficulties in building relationships and building resilience. Keywords: Bandung, PSKW, WTS